Extrajudicial assistance of the European cross-border consumer - Carrizo Aguado, David (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
In the field of e-commerce, ADRs are presented as the most appropriate path for consumers and businessmen to solve, through a single, free web platform, any problems that may arise in their relationships. That is why the promotion of alternative dispute resolution is essential, as it is the most appropriate means to resolve disputes arising from continuous breaches arising from contracts concluded electronically. Going to court involves complexity, expenses and delays that in most cases must support the consumer. Encouraging the use of such methods would be a boost to commercial and consumer online activity by providing agile and economic mechanisms for the resolution of disputes that may arise in transnational commercial transactions. With the arrival of Law 7/2017, of November 2, fruit of the delayed transposition of Directive 2013/11 / EU, consumers residing in the EU are guaranteed access to mechanisms for alternative dispute resolution in matters of consumption of high quality for being independent, impartial, transparent, effective, fast and fair. The European Commission will cooperate with the national authorities to solve technical problems and maximize the use of the ODR platform with a view to strengthening its contribution to the development of the digital single market.